Redesenvolvimento de um medicamento injetável utilizando conceitos Quality by design (QbD) e Design of experiments (DoE) - Aguilar, Michele Cristina Alecrim de Lima (2024)
This study redeveloped a similar pharmaceutical product with a combination of two active ingredients in the form of an injectable solution. The experimental part used the Quality by Design (QbD) approach with the aim of obtaining a greater understanding of the product and process, aiming to reduce the risks of deviations during the commercial manufacture of the medicine. Due to the difficulty of stabilizing the content of one of the active ingredients, which is labile in solution in the presence of heat, light and oxygen, this redevelopment presents a considerable challenge, therefore, the use of QbD is recommended. Formulation and process variables with potential impact on product quality attributes were defined using the Cause and Effect Matrix risk analysis tool. Over time, forty-nine experiments were carried out on a laboratory scale (6.5 L) using experimental planning (Design of experiments, DoE), with the aim of defining and optimizing qualitatively and quantitatively the excipients and evaluating the impact of the variables of process. All formulations were analyzed immediately after carrying out the experiments and after exposing the samples to a forced degradation study (60°C/75%RH for 14 days). The responses (Critical Quality Attribute, CQAs) evaluated in the experiments were: reduction in the content of the two active ingredients and less formation of impurities after forced degradation studies. The experiments demonstrated that: (i) active 1 is stable and the variables are irrelevant at the levels tested, (ii) the presence of antioxidant excipients 1 or 2 reduces the degradation of active 2 and the formation of its known impurity, without differentiation between them , with excipient 2 being defined because it is used in another company medicine and historically stable and (iii) the formulation with potassium salt was defined since experiments with this salt had less formation of unknown individual impurities of active ingredient 2. New experiments were carried out to quantitatively verify the two excipients defined in the first screening study and experiments were carried out evaluating the critical process parameters, and in the range studied, robustness was observed in the process, that is, no variable proved to be relevant.